If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6r-3(6-3r)=4(1-3r+5)
We simplify the equation to the form, which is simple to understand
6r-3(6-3r)=4(1-3r+5)
Simplifying terms in parentheses
6r-3*(6-3r)=4*(+6-3r)
Reorder the terms in parentheses
6r+(-18+9r)=4*(+6-3r)
Remove unnecessary parentheses
+6r-18+9r=+4+*(+6-3r+)
Reorder the terms in parentheses
6r-18+9r=+(+24-12r)
Remove unnecessary parentheses
+6r-18+9r=+24-12r
We move all terms containing r to the left and all other terms to the right.
+6r+9r+12r=+24+18
We simplify left and right side of the equation.
+27r=+42
We divide both sides of the equation by 27 to get r.
r=1.55555555556
| 2x+4(x+1)=6(x+2)3 | | xsqr+24+xsqr+9=5 | | -1/2(1-3)=1/3(2+1) | | [4y-3x-2y][4y+3x+2]= | | 2/3h-1/3h+11-8 | | m+1/2=8 | | -7(-8n+2)=6(7+8n) | | -7(9a-4b+6c)= | | 8/10-7/10 | | 1/7(a-3)(7a+4)=0 | | (4x^2)(3x^5)= | | -3(3y-10)+2(2y+5)= | | 255=x | | 5m+32=5+8(m+6) | | 2+25y-5y^2=x | | -7(n+6)=3(n+6) | | 4(8+r)=4r+32 | | 35=0.5*7 | | 4(7-7x)=28+6x | | 2(4x-.50)=3(x-2) | | 190=60t-5t^2 | | 1/2+5/2 | | -3y=12-2x | | 3(2z-25)-2(z-1)=78 | | 20=4x+3x | | -6(n+1)-2(1-8n)=n-7+8 | | 6+4m=5(m+1) | | 3y+2x=2(y-2x) | | 6(x+9)=8x+8-2x+46 | | 63(5x+4/9)=6(50x-1/3) | | 10+3n=14 | | 6x-9=6(x+9) |